2023
DOI: 10.1007/s40259-023-00633-2
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Amyloid Monoclonal Antibodies for the Treatment of Alzheimer’s Disease

Jeffrey Cummings,
Amanda M. Leisgang Osse,
Davis Cammann
et al.

Abstract: Two monoclonal antibodies (mAbs), aducanumab and lecanemab, have received accelerated approval from the US FDA for initiation of treatment in early Alzheimer's disease patients who have proven β-amyloid pathology (Aβ). One of these, lecanemab, has subsequently received full approval and other monoclonal antibodies are poised for positive review and approval. Anti-amyloid mAbs share the feature of producing a marked reduction in total brain Aβ revealed by amyloid positron emission tomography. Trials associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(26 citation statements)
references
References 75 publications
0
26
0
Order By: Relevance
“…Disease-modifying therapies have been introduced for treatment of AD and have been shown to slow disease progression by approximately 30% . With reduced AD pathology, decreased emergence or improvement of NPSs may be observed as demonstrated in studies of aducanumab .…”
Section: Discussionmentioning
confidence: 99%
“…Disease-modifying therapies have been introduced for treatment of AD and have been shown to slow disease progression by approximately 30% . With reduced AD pathology, decreased emergence or improvement of NPSs may be observed as demonstrated in studies of aducanumab .…”
Section: Discussionmentioning
confidence: 99%
“…Afterwards, the FDA granted breakthrough status to Lecanemab and Donanemab, in order to speed up their approval [50], which finally resulted in full FDA approval of Lecanemab in the U.S. and more recently in Japan. Furthermore, Lecanemab is currently undergoing regulatory review in the European Union (EU), United Kingdom, South Korea, and Canada, while Donanemab is reviewed in the EU and the U.S [7]. Recent exploratory post hoc modeling based on phase III RCT of Donanemab suggested that Aβ levels in immunized patients would remain below the positivity threshold for almost 4 years without the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of binding the N-terminus of fulllength Aβ, Donanemab targets the N-truncated pyroglutamate Aβ (at position 3), present only in Aβ plaques. It is reported to rapidly induce plaque removal and reduce cognitive decline in patients with early symptomatic AD [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Dear Editor, Recently, the US Food and Drug Administration (FDA) approved two anti-amyloid antibodies for the treatment of patients with early Alzheimer's disease (AD), with a third expected to be approved soon. 1 These drugs are designed to remove amyloid-β peptides from the brains of patients in the early stages of AD to slow down cognitive decline. The use of anti-amyloid immunotherapy has raised several ethical issues, mostly centered around the dimensions of beneficence, nonmaleficence, and informed consent.…”
Section: E T T E R Ethical Considerations For the Use Of Anti-amyloid...mentioning
confidence: 99%